IDENTIFIKASI KARAKTERISTIK DAN PEMETAAN TINGKAT KEKUMUHAN KAWASAN PERMUKIMAN KUMUH GAMPONG PANGGONG KECAMATAN JOHAN PAHLAWAN - Cut Suciatina Silvia (Universitas Teuku Umar, 2017)
Identification characteristics of the slums area need can be done for each region. the purpose of this identification to know exactly the problems that existed in the village of Panggong. Identification of problems with the review of indicators and parameters of untidiness. And then will be resulting strategy handling for location or region that have a problems of slum. The identification in this research is performed only on the physical aspects, and observation is done directly in the field. Analysis Methods the level of untidiness and determination of the slums area is done with comprehensive analysis method. The level of untidiness and deliniasi regions of slum obtained, further analysis is done with a matrix of issues and handling that will be done. The results identification of the characteristics of the slums area indicates that the problem most dominant are present on the parameters irregularity of the building 75%, the road is not worthy of 61%, and waste water problems fused with the drainage environmental of 100%. The Results from study of the problems further is done of calculation to obtain the level of untidiness Gampong Panggong obtained 59% or the level of untidiness is medium. Handling for the problem of slums area is done with zoning as a step in determine the zone of priority handling, where is a zone of priority handling problems of slums area in zone 1. Keywords: characteristics of the slums area, identification of the slums area, The level of untidiness, handling the slums area